The Acute Effect of Different Cluster Set Intra-Set Rest Interval Configurations on Mechanical Power Measures During a Flywheel Resistance Training Session - Shane Ryan; Declan Browne; Rodrigo Ramirez-Campillo; Jeremy Moody; Paul J. Byrne (Sports)
The aim of this study was to compare the acute effect of three cluster set (CS) intra-set rest intervals (15 s, 30 s, and 45 s) on mechanical performance measures during a flywheel resistance training session. Twelve amateur male field sport athletes attended three training measurement sessions (separated by 14 days of wash-out), consisting of four sets of nine repetitions (as cluster-blocks: 3 + 3 + 3), using a 0.050 kg·m−2 inertial load. The flywheel quarter-squat (QS) and the flywheel Romanian deadlift (RDL) were selected as resistance training exercises. Participants were randomly allocated different CS intra-set rest durations: 15 s, 30 s, or 45 s. The mean power (MP), peak concentric power (PPcon), peak eccentric power (PPecc), and eccentric overload (EO) were measured. A two-way (within–within) repeated-measures ANOVA reported that MP, PPcon, PPecc, and EO achieved similar values during the QS and RDL sessions involving 30 s and 45 s CS intra-set rest durations. It was noted that the first set did not always result in the greatest performance output for the 30 s and 45 s intervals. Compared to 15 s, the 30 s and 45 s CS intra-set rest durations showed greater MP, PPcon, and PPecc during set 2 (all p ≤ 0.05), set 3 (all p < 0.001), and set 4 (all p < 0.001) for both QS and RDL, and greater EO in the QS exercise (the four sets combined). Compared to shorter (15 s) cluster set intra-set rest intervals, longer (30–45 s) configurations allow greater physical performance outcome measures during flywheel QS and RDL resistance training sessions. The implications for longer-term interventions merit further research.